Adoption of e-business: patterns and consequences of network externalities - Christian Schade; Philipp Köllinger (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
The paper analyzes the adoption of various e-business technologies. Strong empirical evidence is found for the existence of increasing returns to adoption due to indirect network externalities between related technologies. If a company is close to the technological frontier, its probability of adoption increases. The empirical analysis is based on more than 5,000 observations from a cross-sectional European enterprise survey conducted in June 2002. A classification and regression tree (CART) is used to illustrate technological complementarities and their effect for the adoption probability of a firm.
Keywords: O30; L29; C14; 330; Technology Adoption; Path Dependence; Classification Trees